AB0123 Increase in serum levels of srankl and SRANKL/OPG but stable CTX-I in patients with infliximab-treated active ankylosing spondylitis. (23rd January 2014) - Pullerits, R.; Mörck, B.; Bremell, T.; Forsblad d'Elia, H.
Abstract : Background: Ankylosing spondylitis is characterised by an increased pathological bone formation in the spine in association with increased prevalence of osteoporosis. The effect of treatment with TNF-inhibitors on syndesmophyte formation is disputed. Objectives: To study the effect of infliximab treatment on biomarkers of bone metabolism in patients with HLA-B27 positive active ankylosing spondylitis (AS) in a prospective trial. Methods: The patients (n=19) fulfilling the modified New York criteria for definitive AS were treated with infliximab 5 mg/kg for totally 52 weeks. Patients received concomitantly methotrexate (median dose 7.5 mg/week) and NSAIDs on demand. After having completed the first year, the dosage of infliximab was reduced to 3 mg/kg and median infusion interval extended to every 8 weeks and patients were followed up on a regular basis. The blood samples were obtained at baseline before treatment initiation and 2 years after infliximab dose reduction and were stored in -20° until the time of analysis. Serum levels of the biomarkers Wingless proteins (Wnt3a), Dickkopf-1 (Dkk-1), sclerostin, soluble receptor activator of nuclear factors-κB ligand (sRANKL), osteoprotegerin (OPG), interleukin 6 (IL-6), soluble IL-6 receptor (sIL-6R) and C-terminal telopeptide of type I collagen (CTX-I) were measured with sandwich enzyme-linked immunosorbent assays (ELISA). Results: Fourteen men and 5 women (mean age 39±9 and mean disease duration 6.9±7.0 years; median BASDAI at inclusion 6.5 (interquartile range 5.4 – 8.0) were studied. Eighteen patients were followed up at 1 year and 15 patients completed the study at 2 years. Significant reductions in BASDAI score and inflammatory parameters were observed during the first year in comparison with baseline and the treatment effect was preserved throughout the second year after infliximab dose reduction. Two years after infliximab dose reduction 12 patients continued with this treatment regimen. We observed a significant decrease in IL-6 levels (2.55 vs. 0.91 pg/ml, p=0.003) and soluble IL-6 receptor (63097 vs. 51781 pmol/l, p=0.034) in their serum as compared to baseline. In addition, the levels of soluble RANKL increased significantly (p=0.0098) in comparison with study baseline (113.3 vs. 260.5 pmol/l) and also a significant increase in sRANKL/OPG ratio was observed (median 33.75 vs. 52.40, p=0.027). No significant changes were observed regarding Wnt3a, Dkk-1, sclerostin, CTX-I and OPG. Conclusions: Our results show a decrease in the serum markers of inflammation, IL-6 and sIL-6R in association with reduced clinical disease activity. Soluble RANKL and sRANKL/OPG ratio were increased during treatment with infliximab indicating an enhanced osteoclast activity, while serum levels of CTX-I remained unchanged. These intriguing findings need to be elucidated in a larger controlled trial. Disclosure of Interest: None Declared